A beguiling serpent in the protected zone of collecting bargaining : dimissal to enforce demands - Nevhulamba, Fightwell (My University, 2022)
This study examines the relationship between automatic unfair dismissal under Section 187(1)(c) of the Labour Relations Act,1 and dismissal for operational reasons under Section 189 of the LRA. Dismissal is automatically unfair if the reason for dismissal is a refusal by employees to accept a demand in respect of any matter of mutual interest between them and their employer and this is according to Section 187(1)(c) of the LRA Employees have the right to refuse the new terms and conditions of employment, and they cannot be dismissed for doing so. However, if the employer’s business is in decline and thus causes financially loss to the employer, the employer may change the operation of the employment in order to sustain the employment. The employer must initiate consultation process (collective bargaining) with the employees' representatives in order to reach an agreement that protects both the employer's and the employees' interests. To avoid retrenchment, the employer and the employees’ representatives through collective bargaining have to agree to new conditions of the employment and should the parties agree on the new conditions of the employment this will automatically set aside the terms and conditions of the employment contract. In K Ngubane v NTE Limited, 2 “the court observed and noted that the requirement is that the old contract of employment must be terminated with the purpose of inducing acceptance of a demand or proposal, or the employer can simultaneously terminate the contract of employment and give the employee his/her final offer”. Before resorting to dismissal, the employer must exhaust all the alternatives available to him and this could include, inter alia, change of job descriptions since this will not have adverse financial consequences for the workers. If the employees refuse to accept the demands of the employer that were aimed to avoid retrenchments for operational reasons, the employer may dismiss them in accordance with the provisions of section
Thesis (LLM. (Labour Law)) -- University of Limpopo, 2022
Keywords: Dismissal; Employment; Automatic unfair dismissal; Collective bargaining; Employees -- Dismissal of; Collective bargaining -- Law and legislation; Employment conditions.